Study of psychological time dynamics at the age of youth - Valentina I. Volokhova; Marina I. Koshenova; Denis M. Shabanov (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
This paper presents the current trends analysis of research into the psychological time of personality in foreign and domestic psychology, justified the need to study the dynamics of psychological time at the period of youth at conditional points of bifurcation associated with the forced need to make personal choices: in early and late youth. The reasonability of investigating the relationship of psychological time with personal identity as a predictor of self-realisation or maladaptation of personality at the stage of youth is shown. The pilot study presented in this work is aimed at identifying differences in the content characteristics and structure of psychological time in early and late youth. The ascertaining experiment was conducted with two groups (the total number of participants is 50 people). Diagnostic toolkit: the technique of F. Zimbardo on the time perspective (ZTPI), adapted by A. Syrtsova, the technique Time Experience Scale by E.I. Golovakhi, A.A. Kronik, as well as the technique Identity Status according to Marcia in the modification of the questionnaire G. and R. Aminev. Methods of mathematical statistics: t-Students criterion for independent samples and Pearsons index of linear correlation. The data obtained in the pilot study made it possible to draw conclusions that 1) the meaningful characteristics of psychological time in different periods of youth are not identical, 2) the characteristics of psychological time significantly correlate with the status of personality identity, and such a relationship is more important precisely in the period of early adolescence. The obtained data provided an opportunity to clarify the further direction of research and to outline the necessary ways of psychological support of the person during his youth in the conditions of modern social reality. For the prevention of maladaptation and destructive realization of the personality in the period of youth, targeted work is proposed with the psychological time of the personality, with the adoption of the past and the planning of the future, the determination of priorities, goal setting and the formation of temporal competence.